Community Infrastructuring as Necessary Ingenuity in the COVID-19 Pandemic. (October 2020) - Greenberg, Day; Calabrese Barton, Angela; Turner, Carmen; Hardy, Kelly; Roper, Akeya; Williams, Candace; Herrenkohl, Leslie Rupert; Davis, Elizabeth A.; Tasker, Tammy
We report on how one community builds capacity for disrupting injustice and supporting each other during the COVID-19 crisis. We engaged long-term community partners (parents, their youth, and local community center leaders) in on-going conversation on their experiences with the pandemic. We learned with and from community partners about how and what people in communities most vulnerable in this crisis learn about and respond to COVID-19 in highly contextualized ways, individually and through extended family groups and trusted social networks. We report on how they put understandings towards educated, organized, urgent community infrastructuring actions within informal coalition networks. We explore these actions as necessary localized responses to systemic neglect from dominant institutional infrastructures during a global pandemic.